Dinitrogen activation on graphene anchored single atom catalysts: local site activity or surface phenomena - Maibam, Ashakiran; Govindaraja, Thillai; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2019)
Catalysis on two-dimensional (2D) substrates with metal clusters or centers is generally dealt with as a surface phenomenon under the conjecture that the delocalized electron density is the driving force. When single atom catalysts (SACs) are anchored on such materials with delocalized electron density, for instance graphene, the stimulant for catalysis may be either the d-electrons on the metal or the system altogether. To understand the contributing factors of catalysis on such systems, a case study of dinitrogen (N-2) activation on Mo anchored graphene has been made by employing periodic and finite models of graphene. The periodic model represents a continuum of SACs anchored periodically on graphene, while the finite models are graphene nanoflakes of varying sizes and edge orientations. In addition to the physical aspects, such as size/finiteness of graphene, the influence of varying chemical compositions of the substrate on the activity is also evaluated by doping graphene with different B and N concentrations. This study, while clearly bringing out the connotation of regulating atomic composition of graphene substrate for dinitrogen activation, also surprisingly unveils the relative insignificance of varying the size and edge effects of the substrate. These features are highlighted through an analysis of red shift in the N-N stretching frequency, charge transfer to dinitrogen from the catalytic system, and structural and electronic characteristics of the catalytic system. The total and projected density of states plots reveal hybridization between the metal d orbitals and the p orbitals of carbon and nitrogen in the valence band. On the other hand, the frontier molecular orbital analysis also depicts a strong chemisorption of dinitrogen with the metal-graphene supports on account of direct hybridization between the d orbitals of the supported metal atom and the p orbitals of dinitrogen. The Bader and Lowdin charge distribution on the adsorbed dinitrogen in periodic and finite models shows the preeminence of local site over the surface activity.

Unsymmetrical squaraine dyes for dye-sensitized solar cells: position of the anchoring group controls the orientation and self-assembly of sensitizers on the TiO2 surface and modulates its flat band potential - Singh, Ambarish Kumar; Maibam, Ashakiran; Javaregowda, Bharathkumar H.; Bisht, Rajesh; Kudlu, Ashwath; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Physical Chemistry C, 2020)
The position of the anchoring group is systematically changed with a series of alkyl group wrapped donor-acceptor-donor (D-A-D) based squaraine dyes, 4-SQ to 7-SQ, for the use in dye-sensitized solar cells (DSSCs). By this approach, the orientation as well as the self-assembly of the sensitizers can be controlled on the semiconducting TiO2 surface. All of the dyes functionalized with hydrophobic alkyl groups at sp(3)-C and N atoms of the indoline units that is far away from the TiO2 surface to control the self-assembly of dyes and passivate the surface. Controlling both the orientation as well as the self-assembly of the sensitizers synergistically enhances the V-oc of the DSSC device by imparting the dipole moment on the TiO2 surface and minimizing the interfacial charge recombination process of electrons from TiO2 to the oxidized electrolyte, respectively. Further, the presence of a meta-carboxyl group with respect to the N atom of the indoline donor unit for the dyes 4-SQ and 6-SQ makes them nonconductive for the charge injection process, which sheds light on the importance of through-space electron transfer for the device performance. Emission from the relaxed twisted state was found to be a deactivation pathway for 4-SQ on TiO2 and ZrO2, which revealed the importance of structural factors that promote spatial interaction between the sensitizer and metal oxide surface. Computational studies showed the systematic changes in the dipole moment for the sensitizers 4-SQ, 5-SQ, and 6-SQ upon anchoring to the TiO2 surface. The DSSC device performance varied with the position of anchoring groups in the sensitizers. The DSSC device performance of 5-SQ indicates a J(sc) value of 11.35 mA cm(-2), V-oc of 0.698 V, and ff of 77% corresponding to a power conversion efficiency of 6.08% in the presence of 3 equiv of coadsorbent CDCA, which is nearly 1.5 times higher than 6-SQ (V-oc 0.7 V, J(sc) 7.76 mA cm(-2), ff 76%, and eta 4.14%) and 2.6 times higher than 4-SQ (V-oc 0.658 V, J(sc) 4.42 mA cm(-2), ff 78%, and eta 2.28%). IPCE studies revealed the importance of orientation for the charge injection and self-assembly of dyes, as devices with 5-SQ and 6-SQ as a sensitizer showed 94 and 77% response at 578 nm, respectively, which correspond to the aggregated structure of the dye. Mott-Schottky and IPCE experiments showed that the orientation of sensitizers could modulate the V-oc due to the shift in the flat band potential of TiO2.

Durable metalloporphyrin 2D-polymer for photocatalytic hydrogen and oxygen evolution from river and sea waters - Ranjeesh, Kayaramkodath Chandran; George, Leena; Maibam, Ashakiran; Krishnamurty, Sailaja; Babu, Sukumaran Santhosh (ChemCatChem, 2021)
It is highly imaginary that the outcome of a combination of two complementary resources leads to answer an alarming global issue. One such possible example is the solar seawater splitting for `clean fuel' H-2 generation. Since the catalytic activity and stability of the photocatalysts are substantially challenged in seawater, the design of an efficient and stable photocatalyst is highly desirable. Herein, we demonstrate the solar seawater splitting by a two-dimensional polymer catalyst derived from metalloporphyrin bearing multi-hydroxyl groups. A bimetallic (Co and Ni) porphyrin 2D-polymer exhibits excellent long-term durability of 15 cycles of H-2 and O-2 generation in 200 days from pure water without a considerable decrease in efficiency. Detailed studies using river and seawaters also show the reliable performance of the catalyst over repeated cycles. Here the deactivation modes of catalytic activity have been nullified by the layered metalloporphyrin polymer structure through stable pi-pi stacking, signifying the molecular design of 2D-polymer photocatalyst.
Keywords: 2D-polymer; Photocatalyst; porphyrin; Self-assembly; water splitting

Electrocatalytic nitrogen reduction directed through the p-band center of boron on BSAC@Mo2C - Maibam, Ashakiran; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Materials Advances, 2021)
Greener modes of ammonia synthesis via the electrocatalytic route have been investigated on pristine and defective Mo2C based monolayers anchored with metal-free boron atom catalysts. Boron single atom catalysts (SACs) on the defective Mo2C monolayer has been found to activate N2 strongly with an adsorption energy of −1.92 eV and reduce it to NH3 efficiently with a significantly low overpotential of 0.41 eV. The exothermic adsorption of N2 and low overpotential for the nitrogen reduction reduction (NRR) appertain to the p-band center of the boron atom catalyst and charge transfer between the adsorbed N2 and the catalyst, respectively. This work brings forth the correlation between electron occupancy on the boron center and NRR catalytic efficiency on a metal-free SACs@Mo2C monolayer couple, thereby serving as a lead in designing metal free electrocatalysts for the NRR.

Enhanced photocatalytic properties of a chemically modified blue phosphorene - Maibam, Ashakiran; Das, Sawan Kumar; Samal, Pragnya Paramita; Krishnamurty, Sailaja (RSC Advances, 2021)
It is high time to placate the peak demand for an efficient, economic and green fuel in the form of H-2 through photocatalytic water splitting. Several low dimensional materials have been explored for their photocatalytic properties on account of their surface to volume ratio. The present study illustrates the excellent photocatalytic potential of a two-dimensional material, viz. a chemically tempered blue-phosphorene sheet, with single atom thickness and high carrier mobility. Metal-free element, sulphur, is explored as a dopant in a 32-atom blue-phosphorene sheet. The dopant is inserted at three locations viz. central, edge and central edge positions with varying concentrations from 3.125% to 18.75% (corresponding to n = 1 to 6 sulphur atoms within a 32-atom blue-phosphorene sheet, P32-nSn). The cohesive energy studies predict the higher stability of even number S doped sheets as compared to their odd counterparts. Photocatalytic activity is studied in terms of band gap and band alignment for different concentrations of the former. Studies reveal that edge doping demonstrates better water molecule activation independent of S atom concentration. The edge doped systems not only provide the chemical activity to activate water, but also show feasible HER overpotentials of 1.24-1.29 eV at neutral medium. Finally, this work opens up a driving lead of non-corrosive catalysts for water molecule splitting.

Exploring edge functionalised blue phosphorene nanoribbons as novel photocatalysts for water splitting - Maibam, Ashakiran; Chakraborty, Debalina; Joshi, Krati; Krishnamurty, Sailaja (New Journal of Chemistry, 2021)
Hydrogen gas, a highly combustible and eco-friendly fuel is stealing the limelight and its production is one of the major areas of research. An efficient and green method for producing clean hydrogen gas with no harmful by-product is water splitting. With the introduction of low dimensional materials, water splitting has become an easier and cost-effective process. The present work demonstrates the application of one such low dimensional material viz., edge functionalised Blue Phosphorene Nano-Ribbons (BPNRs) as potential photocatalysts. With a carrier mobility of 10(3) cm(2) V-1 s(-1) and a band gap of 1.5-3.0 eV, BPNRs are an attractive candidate for photocatalysis. BPNRs with different edge oreintations, viz. zigzag and armchair are functionalised with CH3O, COOCH3, CHO, COOH, OH, NH2, CONH2, SH, C6H5, and NO2 groups. Their performance towards activating water molecules at different sites on the nanoribbon is studied. The functionalised edges of the BPNRs are the active sites showing similar to 1.2% to 3.2% efficiency in activating the O-H bond of the water molecule. Among the different groups explored, CONH2 functionalised zigzag BPNR clearly exhibits a higher potential towards the adsorption of water molecules (-0.98 eV) and activation of O-H bonds with an elongation of 3.2% and a red shift of 500.6 cm(-1). This is attributed to the lone pair of electrons on the nitrogen atom contributing to the electron donating nature of the CONH2 functional group.

Finite temperature behavior of carbon atom-doped silicon clusters: depressed thermal stabilities, coexisting isomers, reversible dynamical pathways and fragmentation channels - Joshi, Krati; Maibam, Ashakiran; Krishnamurty, Sailaja (New Journal of Chemistry, 2021)
Silicon carbide clusters are significant due to their predominant occurrence in meteoric star dust, particularly in carbon-rich asymptotic giant branch stars. Of late, they have also been recognized as nanoclusters with potential applications in technology. Them both being elements of the same group, there is excellent potential for precise control over the physico-chemical properties of such molecular length-scale materials through atomic engineering and this has been explored recently by various experimentalists. This report simulates one of the significant physical properties, viz. conformational stability, of various carbon-doped silicon clusters as a function of temperature using Born-Oppenheimer molecular dynamics methodology. Single carbon atom-doped silicon clusters with 4-9 atoms (i.e., Si3C-Si8C) are chosen for this study as the gas phase geometries of these clusters have been characterized using a combination of experimental and theoretical methods in the recent past. The simulations ratify that various conformations do not interconvert among themselves at 300 K. The interconversion occurs at 500 K or above, thereby ratifying the possibility of the coexistence of multiple conformations of a given cluster, which are generally synthesized under subroom temperature conditions. Furthermore, the above single carbon atom-doped silicon clusters: (a) have depressed thermal stabilities as compared to their pristine counterparts with the exception of a Si5C conformation; (b) undergo multifarious evolution of the cluster, through the reversible dynamical and fragmentation pathways as a function of temperature and (c) single carbon atom-doped silicon clusters with 7 atoms (starting from Si6C) and above undergo a fragmentation at nearly 2000 K. The underlying electronic and structural properties of various clusters are discussed to explain the above observations with a note on critical fragmentation energy barriers required for the segmentation of clusters with seven or more atoms.

Nitrogen activation to reduction on a recyclable V-SAC/BN-graphene heterocatalyst sifted through dual and multiphilic descriptors - Maibam, Ashakiran; Krishnamurty, Sailaja (Journal of Colloid and Interface Science, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Efficient reduction of nitrogen to ammonia at a minimal cost would require a recherche catalyst tailored by assimilating the inherent electronic and reactive nature of Single Atom Catalysts (SACs) on heteroatom doped-graphene. A full-scale DFT study accounting for disparate descriptions of atomic orbitals and representation of support, has been carried out to identify the most active and recyclable SAC/B-graphene composite as catalyst for Nitrogen Reduction Reaction (NRR). Dual and Multiphilic descriptors derived reactivity pattern of six different metal SACs V, Fe, Ni, Ru, W and Re on periodic and non-periodic paradigms of pristine and BN-pair doped graphene supports, align with the calculated chemisorption efficacy and activation of N<span style="box-sizing: inherit; font-size: 12px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. The enzymatic route of nitrogen reduction on three most ideal metal SACs (V, W and Re) culminates Vanadium SAC, a relatively cheaper metal, anchored on BNring-graphene with an energy barrier of ⩽1.24 eV as a highly active and recyclable catalyst for NRR.

Doped 2D VX2 (X = S, Se, Te) monolayers as electrocatalysts for ammonia production: a DFT based study - Maibam, Ashakiran; BabaRao, Ravichandar; Krishnamurty, Sailaj A. (Applied Surface Science, 2022)
Electrocatalytic nitrogen fixation under ambient conditions on vanadium dichalcogenides (VX2) with non-metal dopants has been explored herein. Understanding the interface chemistry, inherent electronic and acute synergistic nature of non-metal dopants on two unique phases of VX2 has been meticulously explored through a scrutiny of several non-metal atoms as catalytic centers. The efficacity of N-2 chemisorption and N-N bond activation has been implemented as crucial parameters to realize boron and carbon doped VX2 monolayers to be electrocatalytically active for nitrogen reduction reaction (NRR). Detailed investigation on the NRR mechanism brings out the pivotal role of thermodynamic favourability for product formation obtained from Gibbs free energy differences. The charge transfer on N and pi-pi* orbital hybridization and electron ``donor-acceptor `` mechanism between the non-metal and N-2 has been found to modulate the electrocatalytic barrier for NRR on VX2 monolayers. This study proposes boron doped VS2 as an efficient chemically feasible, earth abundant sustainable electrocatalyst for NRR with an overpotential as low as 0.06 eV.
Keywords: 1T and 2H phases; DFT; electrocatalysts; Nitrogen Reduction Reaction; Non metal dopants; Vanadium dichalcogenides

High-alkaline water-splitting activity of mesoporous 3D heterostructures: an amorphous-shell@crystalline-core nano-assembly of Co-Ni-phosphate ultrathin-nanosheets and V- doped cobalt-nitride nanowires - Singh, Thangjam Ibomcha; Maibam, Ashakiran; Cha, Dun Chan; Yoo, Sunghoon; BabaRao, Ravichandar; Lee, Sang Uck; Lee, Seunghyun (Advanced Science, 2022)
Introducing amorphous and ultrathin nanosheets of transition bimetal phosphate arrays that are highly active in the oxygen evolution reaction (OER) as shells over an electronically modulated crystalline core with low hydrogen absorption energy for an excellent hydrogen evolution reaction (HER) can boost the sluggish kinetics of the OER and HER in alkaline electrolytes. Therefore, in this study, ultrathin and amorphous cobalt-nickel-phosphate (CoNiPOx) nanosheet arrays are deposited over vanadium (V)-doped cobalt-nitride (V-3%-Co4N) crystalline core nanowires to obtain amorphous-shell@crystalline-core mesoporous 3D-heterostructures (CoNiPOx@V-Co4N/NF) as bifunctional electrocatalysts. The optimized electrocatalyst shows extremely low HER and OER overpotentials of 53 and 270 mV at 10 mA cm(-2), respectively. The CoNiPOx@V-3%-Co4N/NF (+/-) electrolyzer utilizing the electrocatalyst as both anode and cathode demonstrates remarkable overall water-splitting activity, requiring a cell potential of only 1.52 V at 10 mA cm(-2), 30 mV lower than that of the RuO2/NF (+)/20%-Pt/C/NF (-) electrolyzer. Such impressive bifunctional activities can be attributed to abundant active sites, adjusted electronic structure, lower charge-transfer resistance, enhanced electrochemically active surface area (ECSA), and surface- and volume-confined electrocatalysis resulting from the synergistic effects of the crystalline V-3%-Co4N core and amorphous CoNiPOx shells boosting water splitting in alkaline media.
Keywords: core-shell; hydrogen productions; metal nitrides; metal phosphates; synergistic effect; water-splitting

Mapping the finite-temperature behavior of conformations to their potential energy barriers: case studies on Si6B and Si5B clusters - Maneri, Asma H.; Singh, Chandrodai Pratap; Kumar, Ravi; Maibam, Ashakiran; Krishnamurty, Sailaja (ACS Omega, 2022)
Dynamical simulations of molecules and materials have been the route to understand the rearrangement of atoms within them at different temperatures. Born-Oppenheimer molecular dynamical simulations have further helped to comprehend the reaction dynamics at various finite temperatures. We take a case study of Si6B and Si5B clusters and demonstrate that their finite-temperature behavior is rather mapped to the potential energy surface. The study further brings forth the fact that an accurate description of the dynamics is rather coupled with the accuracy of the method in defining the potential energy surface. A more precise potential energy surface generated through the coupled cluster method is finally used to identify the most accurate description of the potential energy surface and the interconnected finite-temperature behavior.

Tantalum based single, double, and triple atom catalysts supported on g-C2N monolayer for effective nitrogen reduction reaction: a comparative DFT investigation - Rasool, Anjumun; Anis, Insha; Dixit, Mudit; Maibam, Ashakiran; Hassan, Afshana; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Catalysis Science & Technology, 2022)
Design of efficient and low cost electrocatalysts for the reduction of N-2 molecule to NH3 in a green manner remains a great challenge in the 21st century. Herein, we have used density functional theory based first principle simulations to systematically investigate the nitrogen reduction reaction (NRR) ability of single, double, and triple Ta-atom catalysts anchored to C2N monolayer. Our results demonstrate that the single and triple Ta-atom catalysts anchored to C2N monolayer act as superior catalysts for the NRR via alternating and distal pathways as compared to the Ru(0001) stepped surface. In particular, the triple Ta-atom catalyst anchored to C2N shows enhanced NRR performance with a limiting potential of -0.72 V which is comparable to the experimentally reported Ru based single atom catalyst. Further, all the three catalysts were found to be highly selective for NRR with an enhanced ability to suppress the competitive hydrogen evolution reaction. Electronic structure analysis revealed that the enhanced ability of Ta-3@C2N catalyst to effectively capture and reduce N-2 molecule could be attributed to the built up of localized d states near the fermi level, thereby aiding in strong electron transfer into the antibonding orbitals of N-2. Thus, our findings propose a highly active catalyst for the NRR with an emphasis on the importance of triple atom-based catalysts for electrocatalytic applications.

Chemical bridge-mediated heterojunction electron transport layers enable efficient and stable perovskite solar cells - Patil, Pramila; Maibam, Ashakiran; Sangale, Sushil S.; Mann, Dilpreet Singh; Lee, Hyun-Jung; Krishnamurty, Sailaja; Kwon, Sung-Nam; Na, Seok-In (ACS Applied Materials and Interfaces, 2023)
Perovskite solar cells (PSCs) emerged as potential photovoltaicenergy-generating devices developing in recent years because of theirexcellent photovoltaic properties and ease of processing. However,PSCs are still reporting efficiencies much lower than their theoreticallimits owing to various losses caused by the charge transport layerand the perovskite. In this regard, herein, an interface engineeringstrategy using functional molecules and chemical bridges was appliedto reduce the loss of the heterojunction electron transport layer.As a functional interface layer, ethylenediaminetetraacetic acid (EDTA)was introduced between PCBM and the ZnO layer, and as a result, EDTAsimultaneously formed chemical bonds with PCBM and ZnO to serve asa chemical bridge connecting the two. DFT and chemical analyses revealedthat EDTA can act as a chemical bridge between PCBM and ZnO, passivatedefect sites, and improve charge transfer. Optoelectrical analysisproved that EDTA chemical bridge-mediated charge transfer (CBM-CT)provides more efficient interfacial charge transport by reducing trap-assistedrecombination losses at ETL interfaces, thereby improving device performance.The PSC with EDTA chemical bridge-mediated heterojunction ETL exhibiteda high PCE of 21.21%, almost no hysteresis, and excellent stabilityto both air and light.
Keywords: charge transfer; chemical bridge; electron transport layer; ethylenediaminetetraacetic acid; Perovskite solar cells; trap-assisted recombination

Critical review on amorphous-crystalline heterostructured electrocatalysts for efficient water splitting - Singh, Manjinder; Cha, Dun Chan; Singh, Thangjam Ibomcha; Maibam, Ashakiran; Paudel, Dasu Ram; Nam, Dong Hwan; Kim, Tae Hyeong; Yoo, Sunghoon; Lee, Seunghyun (Materials Chemistry Frontiers, 2023)
Introducing complementary active materials in tandem as heterostructures of various shapes and sizes can significantly improve the physicochemical properties of the developed materials. Recently, the use of amorphous materials in conjunction with crystalline moieties as highly efficient electrocatalysts for water-splitting electrolyzers has surged rapidly. Excellent bifunctional activity for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) can be achieved from amorphous-crystalline-based materials owing to their remarkably conductive crystalline phase as well as their long-range disordered amorphous phase. In addition, the high specific surface area, disordered structure, and enhanced structural stability can accommodate various defects and strains that develop during in situ electrochemical reactions. Consequently, amorphous materials can be used as both surface-confined and volume-confined electrocatalysts. Although crystalline materials have better electronic properties as well as higher thermal and mechanical stability, they suffer from limited activity due to only surface-confined electrocatalysis. In this regard, the judicious integration of crystalline and amorphous active materials suitable for the OER and HER can tremendously enhance their bifunctional electrocatalytic activities owing to their synergistic effects. The variety in the choice of amorphous and crystalline counterparts presents ample opportunities for further exploration of the development of amorphous-crystalline heterostructured materials with unique properties. However, considering the recent massive developments in the understanding and protocols for fabricating such heterostructures, a critical review is vital for further advancement in this direction. Although some review papers have focused only on amorphous materials, including their synthesis methods, properties, and applications, no critical review that provides an overview emphasizing amorphous-crystalline heterostructures for electrocatalytic water-splitting applications has been published. In this regard, this review aims to present comprehensive details on the recent developments in the fabrication of different amorphous-crystalline heterostructures, the choice of the composition of each component, and the resulting physicochemical properties for the OER, HER, and overall water-splitting. It provides an in-depth understanding of amorphous-crystalline material synthesis protocols, their selection rationale, and their targeted physicochemical properties. This review also provides thought-provoking ideas and long-term perspectives for future research. This review presents comprehensive details on recent developments in the fabrication of different amorphous-crystalline heterostructures, their compositions, and the resulting physicochemical properties for OER, HER, and overall water splitting.

D-A-D-based unsymmetrical thiosquaraine dye for the dye-sensitized solar cells(dagger) - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Photochemistry and Photobiology, 2023)
In dye-sensitized solar cell, modulating the electronic properties of the sensitizer by varying the donor, pi-spacer, acceptor and anchoring groups help optimizing the structure of the dye for better device performance. Here, a donor-acceptor-donor-based unsymmetrical thiosquaraine sensitizer (SQ5S) has been designed and synthesized. Photophysical, electrochemical, theoretical and photovoltaic characterizations of SQ5S dye have been compared with its oxygen analog, SQ5. The incorporation of the sulfur atom in the acceptor unit of SQ5S dye showed an intense peak at 688 nm, which was 38 nm of red-shifted and showed the panchromatic light harvesting response with the onset of 850 nm compared with SQ5 dye. The LUMO and HOMO energy levels are well aligned with the conduction band of TiO2 and the redox potential of electrolyte for the charge injection and the dye-regeneration processes, respectively. Photovoltaic efficiency of 1.51% (V-OC 610 mV, J(SC) 3.07 mA cm(-2), ff 81%) has been achieved for SQ5S dye, whereas SQ5 showed the device performance of 5.43% (V-OC 723 mV, J(SC) 9.3 mA cm(-2), ff 80%). The decreased device performance for the dye SQ5S has been attributed to the favorable intersystem crossing process associated with the photoexcited SQ5S that reduces the driving force for the charge injection process.

Electrocatalytic nitrogen reduction on defective graphene modulated from single atom catalyst to aluminium clusters - Maibam, Ashakiran; Krishnamurty, Sailaja; BabaRao, Ravichandar (Applied Surface Science, 2023)
Density Functional Theory (DFT) investigation on the most earth-abundant Al-based catalysts, has been conducted detailing its electronic properties and catalytic efficacy for nitrogen reduction at ambient condition. The Al-based catalysts have been modulated to perform as par a highly performing, but rare, Ru-single atom catalytic center by varying number of Al atoms, shape, and size. The coalesce of band-center, work function and electronic properties in metal atom catalysts along with N-N bond activation has been demonstrated to be responsible for an efficient nitrogen reduction reaction (NRR) with Delta Gmax of 0.78 eV in Al5 supported on N-doped double vacancy graphene (Al5@N4-DVG) catalyst. Electron localization function analysis has shown a weak physisorption of N2 in the Al-based catalysts. Projected Density of States (PDOS) illustrates the enhancement of aluminium electron density in Al5@N4-DVG led to enhanced orbital densities overlap of Alp and Np electrons. The Bader charge analysis and electronic analysis of the intermediates show efficient electron gain on the N atoms, leading to formation of NH3 from the NxHy intermediates in Al5@N4-DVG catalyst.

High rate, high temperature, dendrite free plating/stripping of Li in 3-dimensional honeycomb boron carbon nitride to realize an ultrastable lithium metal anode - Patrike, Apurva; Karbhal, Indrapal; Wasnik, Kundan; Torris, Arun; Maibam, Ashakiran; Krishnamurty, Sailaja; Shelke, V, Manjusha (Journal of Energy Storage, 2023)
Lithium (Li) metal could be the anode of choice for energy dense Li-batteries owing to its high theoretical specific capacity. However, low coulombic efficiency and poor safety on account of the occurrence of the Li-dendrites during charging-discharging pose a bottleneck for practical applications. In this work, we report a high-rate plating and stripping of Li through host engineering to realize ultrastable Li metal anode (LMA). Benchmark plating/stripping efficiency could be achieved via uniquely structured, highly ordered honeycomb boron carbon nitride (HBCN) as a functional scaffold. Boron and nitrogen doping, large surface area and ordered mesoporous structure induce homogeneous solid electrolyte interface (SEI) layer formation and provide numerous nucleation sites with subsequent dendrite-free growth with 99.98 % coulombic efficiency at 8 mA cm(-2) high current and 10 mAh cm(-2) capacity over 3000 cycles. Via post-cycling advanced characterizations techniques of Ex-situ XPS, 3D X-ray micro-tomography analyses and FESEM, we demonstrate the formation of a stable SEI layer and morphological changes that occurred during Li plating cycles in the HBCN structure. Computational studies validate the high lithium plating-stripping efficacy of HBCN to its highly ordered porous nature, exothermic Li-binding and upshift in the Fermi levels. When tested at elevated temperature (50 degrees C), a stable Li plating-stripping in HBCN is realised at 4 mA cm(-2) current and 10 mAh cm(-2) capacity values with similar to 100 % C.E. Furthermore, we report the results of testing a Li metal cell comprised of Li deposited HBCN anode and LiFePO4 (LFP) cathode.
Keywords: Boron carbon nitride; Dendrite-free Li metal anode; Functional scaffold; High temperature plating/stripping of Li; Molecular planarity parameter; X-ray micro-tomography

Metal-organic framework-derived mesoporous B-doped CoO/Co@N-doped carbon hybrid 3D heterostructured interfaces with modulated cobalt oxidation states for alkaline water splitting - Cha, Dun Chan; Singh, Thangjam Ibomcha; Maibam, Ashakiran; Kim, Tae Hyeong; Nam, Dong Hwan; BabaRao, Ravichandar; Lee, Seunghyun (Small, 2023)
Heteroatom-doped transition metal-oxides of high oxygen evolution reaction (OER) activities interfaced with metals of low hydrogen adsorption energy barrier for efficient hydrogen evolution reaction (HER) when uniformly embedded in a conductive nitrogen-doped carbon (NC) matrix, can mitigate the low-conductivity and high-agglomeration of metal-nanoparticles in carbon matrix and enhances their bifunctional activities. Thus, a 3D mesoporous heterostructure of boron (B)-doped cobalt-oxide/cobalt-metal nanohybrids embedded in NC and grown on a Ni foam substrate (B-CoO/Co@NC/NF) is developed as a binder-free bifunctional electrocatalyst for alkaline water-splitting via a post-synthetic modification of the metal-organic framework and subsequent annealing in different Ar/H-2 gas ratios. B-CoO/Co@NC/NF prepared using 10% H-2 gas (B-CoO/Co@NC/NF [10% H-2]) shows the lowest HER overpotential (196 mV) and B-CoO/Co@NC/NF (Ar), developed in Ar, shows an OER overpotential of 307 mV at 10 mA cm(-2) with excellent long-term durability for 100 h. The best anode and cathode electrocatalyst-based electrolyzer (B-CoO/Co@NC/NF (Ar)(+)//B-CoO/Co@NC/NF (10% H-2)(-)) generates a current density of 10 mA cm(-2) with only 1.62 V with long-term stability. Further, density functional theory investigations demonstrate the effect of B-doping on electronic structure and reaction mechanism of the electrocatalysts for optimal interaction with reaction intermediates for efficient alkaline water-splitting which corroborates the experimental results.
Keywords: 3D heterostructures; B-doped metal-oxides; electrocatalysts; hydrogen evolution reactions; metal-organic frameworks; oxygen evolution reactions

Quantum dot (Aun/Agn, n=3-8) capped single lipids: interactions and physicochemical properties - Maneri, Asma H. H.; Varode, Shruti Suhas; Maibam, Ashakiran; Ranjan, Priyatosh; Krishnamurty, Sailaja; Joshi, Krati (Physical Chemistry Chemical Physics, 2023)
Realizing the potential of nano-hybrid biomaterials in various applications (nanoprobes to drug delivery), special attention has been devoted towards their synthesis and development. Nonetheless, several questions pertaining to the interface chemistry between the constituent entities (biomolecules and organic/inorganic part) of these hybrids, still remain unresolved. Keeping these unsolved issues in mind, the present theoretical investigation focuses on determining the electronic/physicochemical properties and interactions within gold and silver quantum dot-capped single lipid molecules. Quantum dots of varying sizes and shapes have been chosen and then coupled with lipid molecules (1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC), 1,2-dimyristoyl-sn-glycero-3-phosphoethanolamine (DMPE), 1,2-dimyristoyl-sn-glycero-3-phosphoglycerol, sodium salt (DMPG)), at the choline/glycerol, carboxylate and phosphate site. It has been identified that Au Qds interact strongly as compared to Ag clusters. In addition to the type, the shape and size of the Qd also influences their attachment with lipids. Among various sites, the phosphate site provides a considerably stronger platform for the coupling of Qds. On the other hand, attachment at the choline site leads to significantly lower interaction energies. The trend noted in interaction energies coincides with the structure-electronic property analysis (interatomic bond distances, charge transfer, PO2- stretching frequencies), which further helps in deducing the nature of interactions. The molecular dynamics simulations performed on selected Qd-lipid complexes established that the Qd interacting with lipids at the phosphate site remains fairly stable at room temperature without undergoing fragmentation into individual components. On the other hand, at the choline site, the Qd-to-lipid coupling is unstable and therefore they experience disintegration at 300 K temperature. Additionally, a unique glycerol-to-phosphate site crossover is evidenced, which reaffirms that the phosphate site is selectively preferred by Qds for binding with lipid molecules.

Robust zeolitic tetrazole framework for electrocatalytic dopamine detection with high selectivity - Sarfudeen, Shafeeq; Sruthi, Vadakke Purakkal; Maibam, Ashakiran; Panda, Premchand; Jhariat, Pampa; Senthilkumar, Sellappan; BabaRao, Ravichandar; Panda, Tamas (Inorganic Chemistry, 2023)
A novel zeolitic tetrazolate framework (ZTF-8) has been synthesized by solvent-free heat-assisted (70 C-degrees) mechanochemical grinding of zinc acetate and 5-methyl tetrazole in the presence of NaOH powder. The structure of ZTF-8 adopts the zeolitic sodalite (SOD) topology with uncoordinated N-heteroatom sites and resembles the structure of the well-known zeolitic imidazole framework ZIF-8. ZTF-8 is exceptionally stable in 0.1 M aqueous acid and base solutions for 60 days at 25 C-degrees. The unique structure with uncoordinated N-heteroatom active sites and exceptional stability of ZTF-8 facilitated the electrocatalytic oxidation of dopamine to dopamine quinone at neutral pH. Without any postsynthetic modification, ZTF-8 is directly used for the facile electrochemical detection of dopamine over a wide range of concentrations (5-550 mu M) with a high sensitivity (2410.8 mu A mM-1 cm-2). It also demonstrated promising selectivity over other interferents of similar oxidation potential, such as ascorbic acid and uric acid. The DFT study revealed that the ZTF-8 framework has a higher binding energy (-145.07 kJ/mol) and stronger interaction with dopamine than its isostructural ZIF-8 structure (-130.42 kJ/mol).

Steric and electronic effect in unsymmetrical squaraine dyes for dye-sensitized solar cells - Nawghare, Indrajeet S.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of physical chemistry C, 2023)
Functionalizing the light harvesting sensitizers with additional electron-donating or -withdrawing groups is a potential approach to modulate the photophysical and electrochemical properties which in-turn optimizes the driving force associated with the charge injection and dye-regeneration processes at the dye-TiO2/electrolyte interface and the photovoltaic device performance in dye-sensitized solar cells (DSSCs). Furthermore, modulated electronic levels of the dyes provide an opportunity to reduce the overpotential associated with the dye-regeneration process and make the dye-TiO2 interface compatible with various electrolytes. Furthermore, an in-built steric feature by means of introducing linear/branched alkyl groups in the sensitizer is important in controlling the aggregation of dyes on the TiO2 surface. Hence, to integrate both steric and electronic properties, a series of alkyl group-wrapped unsymmetrical squaraine dyes (SQ-X) with electron-donating and -withdrawing groups have been designed, synthesized, and utilized for DSSC device fabrication. These dyes are functionalized with alkyl groups at both sp(3)-C and N-atoms of the indoline donor moiety at the nonanchoring side to have a similar steric feature. Photophysical and electrochemical studies revealed that the HOMO and LUMO energy levels of the SQ-X series of dyes have been modulated systematically with sufficient driving forces for both charge injection and dye-regeneration processes with iodolyte (I-/I-3(-)) electrolyte. In the presence of electron-donating groups in SQ-X (where X = -NPh2 and -OMe), the HOMO energy levels are less positive than SQ-H, whereas the presence of electron-withdrawing groups such as -CO2Me, -CN, and -NO2 pushed the HOMO energy levels toward more positive potentials. Enhanced photovoltaic performances have been obtained for the dyes containing electron-donating groups, where the dye with the -NPh2 group showed a maximum of eta 7.03% (V-OC 708 mV, J(SC) 13.16 mA cm(-2), and ff 78%). The dye with the strong electron-withdrawing group -NO2 showed an efficiency of 1.49% (V-OC = 634 mV, J(SC) = 3.13 mA cm(-2), and ff 75%). As the dyes with the electron-withdrawing group possess deep positive HOMO energy levels, the DSSC device characterization has been investigated with the Cu+/2+ redox shuttle. The reduced device performance of electron-withdrawing-group-containing dyes is due to the unfavored charge distribution in the LUMO compared to the presence of electron-donating-group-containing dyes, and it was supported by the difference in the charge injection efficiency.
Keywords: cobalt; Donor; Dynamics; Organic dyes

Visible-light-active unsymmetrical squaraine dyes with pyridyl anchoring groups for dye-sensitized solar cells - Deshmukh, Shivdeep Suresh; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Langmuir, 2023)
Visible-light-active alkyl group-wrapped unsymmetrical squaraine dyes SD1-SD3 were synthesized, featuring an indoline donor and pyridine and carboxylic acid anchoring groups. Their photophysical, electrochemical, and photovoltaic characteristics were examined by fabricating a dye-sensitized solar cell (DSSC) device. Both carboxylic acid and pyridine anchoring groups containing squaraine dyes SD3 and SD2 possess similar photophysical and electrochemical characteristics. However, their photovoltaic performances were completely different. The SD3 dye with the carboxylic acid anchoring group displayed a DSSC device efficiency of 7.20% (V-OC 0.81 V; J(SC) 12.29 mA/cm(2)) using iodolyte (I-/I-3(-)) electrolyte, compared to SD1 (V-OC 0.659 V; J(SC) 4.97 mA/cm(2); and eta - 2.34%) and SD2 (V-OC 0.629 V; J(SC) 1.68 mA/cm(2); and eta - 0.84%), which were featured with pyridyl anchoring groups. These results were attributed to dye loading on the Lewis and Br & oslash;nsted acidic sites of TiO2 and the importance of aggregated structures for photocurrent generation. In the incident photon-to-current efficiency (IPCE) analysis, SD1 dye-sensitized devices exhibited photocurrent generation from both monomeric and aggregated dyes on the TiO2 surface. In contrast, SD2 showed photocurrent generation solely from aggregated states. Despite the introduction of long alkyl chains to reduce dye aggregation and charge recombination, the results indicated preferential charge injection from only the aggregated SD2 dye on TiO2. Fluorescence-quenching experiments indicated an efficient charge transfer from the aggregated SD2 dye to TiO2 compared to that of the monomeric dye. Cosensitization, a method to enhance the light-harvesting efficiency and photocurrent generation in DSSCs, was explored by simultaneously cosensitizing pyridyl-based dyes (SD1 and SD2) with a blue-colored carboxylic acid-based squaraine dye SD4. IPCE analysis demonstrated that both SD1 and SD4 contributed to generating a photocurrent of 9.11 mA/cm(2). The sequential cosensitization of SD1 and SD4 with the coadsorbent CDCA showed the highest performance, with a V-OC of 0.663 V, a J(SC) of 11.43 mA/cm(2), and an efficiency (eta) of 5.20%.
Keywords: co-sensitization; Design; Emmision; Fluorescent Dyes; High-Efficiency; Organic Dye; Ring

Aniline and indoline donors based far-red active unsymmetrical squaraine dyes for dye sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemphotochem, 2024)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on the metal-oxide surface by appending the alkyl groups around the donor or pi-spacer unit of the dye is a potential approach to enhance DSSC efficiency. Further, rigidification of the dye structures by cyclization modulates the photophysical properties of the sensitizer. Here a series of donor-acceptor-donor (D-A-D) type far-red active unsymmetrical squaraine dyes (SQA) have been designed and synthesized, where N,N-dimethylaniline, methylated- and branched-indoline have been used as donor units. These dyes showed absorption between 629-654 nm (lambda max) with the molar extinction coefficient of 1.49-1.94x105 M-1 cm-1. Systematic enhancements in DSSC device efficiency have been observed due to the cyclization and alkyl-groups incorporation in this set of dyes which were further enhanced with the addition of chenodeoxycholic acid (CDCA). The highest DSSC device efficiency of 4.78 % (Jsc of 8.77 mA/cm2 and Voc of 692 mV) has been achieved for SQA3. The IPCE profile of SQA dyes indicates the contribution of aggregated structures for the photocurrent generation. Further, co-sensitization of SQA3 dye with a complementary visible light active dye AK4 showed the enhanced device efficiency of 6.27 % with panchromatic IPCE response. Dye rigidification, and controlled aggregation of dyes on TiO2 by means of cyclization of donor unit and introducing the alkyl groups in the dye structure synergistically improve the dye-sensitized solar cell (DSSC) device performance. Donor-Acceptor-Donor (D-A-D) based unsymmetrical squaraine dye SQA3 showed the DSSC device performance of 4.78 %.image
Keywords: co-sensitization; dye-sensitized solar cell; effect of alkyl chain; molecular planarity; squaraine dye

Breaking the inactivity of MXenes to drive Ampere-level selective oxygen evolution reaction in seawater - Gbadamasi, Sharafadeen; Loomba, Suraj; Haris, Muhammad; Khan, Muhammad Waqas; Maibam, Ashakiran; Mousavi, Seyed Mahdi; Mahmud, Sofiu; Thomsen, Lars; Tadich, Anton; BabaRao, Ravichandar; Xian, Jian; Mahmood, Nasir (MATERIALS SCIENCE & ENGINEERING R-REPORTS, 2024)
Keywords: 2D heterostructures; Metal-organic framework; Oxygen Evolution Reaction

Heterogeneous acid-base organocatalyst for cascade deacetalisation-knoevenagel condensations - Chhetri, Ashis; Maibam, Ashakiran; Maniam, Subashani; BabaRao, Ravichandar; Wilson, Karen; Lee, Adam F.; Mitra, Joyee (ChemSusChem, 2024)
Multifunctional heterogeneous catalysts are an effective strategy to drive chemical cascades, with attendant time, resource and cost efficiencies by eliminating unit operations arising in normal multistep processes. Despite advances in the design of such catalysts, the fabrication of proximate, chemically antagonistic active sites remains a challenge for inorganic materials science. Hydrogen-bonded organocatalysts offer new opportunities for the molecular level design of multifunctional structures capable of stabilising antagonistic active sites. We report the catalytic application of a charge-assisted, hydrogen-bonded crystalline material, bis(melaminium)adipate (BMA), synthesised from melamine and adipic acid, which possesses proximate acid-base sites. BMA exhibits high activity for the cascade deacetalisation-Knoevenagel condensation of dimethyl acetals to form benzylidenemalononitriles under mild conditions in water; BMA is amenable to large-scale manufacture and recycling with minimal deactivation. Computational modelling of the melaminium cation in protonated BMA explains the observed catalytic reactivity, and identifies the first demethoxylation step as rate-limiting, which is in good agreement with time-dependent 1H NMR and kinetic experiments. A broad substrate scope for the cascade transformation of aromatic dimethyl acetals is demonstrated.
Keywords: Antagonistic acid-base sites; Charge-assisted hydrogen bonding; Chemical cascade; organocatalysis; Sustainable catalysis

Purification of waste-generated biogas mixtures using covalent organic framework's high CO2 Selectivity - Paul, Ratul; Maibam, Ashakiran; Chatterjee, Rupak; Wang, Wenjing; Mukherjee, Triya; Das, Nitumani; Yellappa, Masapogu; Banerjee, Tanmay; Bhaumik, Asim; Venkata Mohan, S.; BabaRao, Ravichandar; Mondal, John (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: CAPTURE; CARBON-DIOXIDE; Efficiency; Energy; Hydrogen; STORAGE

Surface electronic properties-driven electrocatalytic nitrogen reduction on metal-conjugated porphyrin 2D-MOFs - Maibam, Ashakiran; Orhan, Ibrahim B.; Krishnamurty, Sailaja; Russo, Salvy P.; BabaRao, Ravichandar (ACS Applied Materials and Interfaces, 2024)
Two-dimensional (2D) metal organic framework (MOF) or metalloporphyrin nanosheets with a stable metal-N-4 complex unit present the metal as a single-atom catalyst dispersed in the 2D porphyrin framework. First-principles calculations on the 3d-transition metals in M-TCPP are investigated in this study for their surface-dependent electronic properties including work function and d-band center. Crystal orbital Hamiltonian population (-pCOHP) analysis highlights a higher contribution of the bonding state in the M-N bond and antibonding state in the N-N bond to be essential for N-N bond activation. A linear relationship between Delta G(max) and surface electronic properties, N-N bond strength, and Bader charge has been found to influence the rate-determining potential for nitrogen reduction reaction (NRR) in M-TCPP MOFs. 2D Ti-TCPP MOF, with a kinetic energy barrier of 1.43 eV in the final protonation step of enzymatic NRR, shows exclusive NRR selectivity over competing hydrogen reduction (HER) and nitrogenous compounds (NO and NO2). Thus, Ti-TCPP MOF with an NRR limiting potential of -0.35 V in water solvent is proposed as an attractive candidate for electrocatalytic NRR.
Keywords: Density Functional Theory (DFT); electrocatalytic nitrogen reductionreaction; kinetic energy barrier; limitingpotential; Metalloporphyrin; NRR selectivity

Synthesis of Hofmann-based metal-organic frameworks incorporating a bis-pyrazole linker for various gas separations - Matthews, Brooke L.; Harvey-Reid, Nathan C.; Jangodaz, Elnaz; Scott, Victoria-Jayne; Polson, Matthew I. J.; Maibam, Ashakiran; BabaRao, Ravichandar; Telfer, Shane G.; Kruger, Paul E. (JOURNAL OF MATERIALS CHEMISTRY A, 2024)
Keywords: acetylene; C2H2/CH4; Ni; Purification; SPIN-CROSSOVER BEHAVIOR

`Turning on' to glutathione: a rhodamine-based fluorescent chemodosimeter with nanomolar sensitivity - Badekar, Pooja S.; Deo, Harshada S.; Varma, Mokshada E.; Kulkarni, Prasad P.; Maibam, Ashakiran; Krishnamurty, Sailaja; Kumbhar, Anupa A. (ChemistrySelect, 2024)
A new colorimetric and fluorescence turn-on chemodosimeter for selective detection of GSH over Cys and Hcy with 34-fold enhancement in emission intensity is reported. Probe 1 exhibited ultra-sensitivity toward GSH with 0.125 nM detection limit and successfully displayed GSH detection in MCF-7 live cells. The mechanism of sensing is established by density functional theoretical calculations.
Keywords: Chemodosimeter; Fluorescence turn-on; GSH; MCF-7 cells; Rhodamine

Ultra-small Au nanoclusters with tailored photoluminescence properties using modified thiol ligands: a computational and experimental demonstration - Chahande, Anurag M.; Maibam, Ashakiran; Krishnamurty, Sailaja; Devi, R. Nandini (Particle & Particle Systems Characterization, 2024)
Au nanoclusters with tailored photoluminescence can be obtained through controlled nanoparticle ligand interface chemistry. The present work reports molecular gold nanoclusters with tuneable photoluminescence emission from 600 to 700 nm using N,N `,N `'-trialkyl (11-mercaptoundecyl)ammonium chloride ligands as capping-agents. The tunability within red spectral region is regulated through specific interface chemistry between gold nanoclusters of molecular range and functional groups of the quaternary ammonium head over N,N `,N `'-trialkyl(11-mercaptoundecyl)ammonium chloride. Combined understanding obtained from the spectroscopy, microscopy, and density functional theory studies demonstrate that the functional group specific electronic interactions at the interfaces steer the emission characteristics of ``molecular'' Au nanoparticles. The study clearly identifies that bulkier functional groups, i.e., triethyl, tripropyl, tributyl, and dimethyl benzene over N+ (of thiol ligand) through their steric effects minimize the particle size giving rise to tunable photoluminescence emission in red spectral region. However, the red shift seen in the emission Au nanoclusters with N-(11-mercaptoundecyl)-N,N `-dimethylbenzenammonium chloride ligand in contradiction to particle size effect is computationally proved to be due to the delocalization of electron density from benzene aromatic ring to N+ of ammonium head leading to a reduction in the HOMO-LUMO energy gap. Fluorescence properties of water dispersible Au nanoclusters are tuned by varying the ammonium head group. Density Functional Theory studies correlate the distinction in emission when head group is phenyl to charge transfer characteristics. image
Keywords: Density functional theory; photoluminescent Au nanoclusters; surface plasmon resonance; thiol ligand

Unravelling the Cu-Co nanoparticle synergy over Ceria-Zirconia support toward efficient reverse water gas shift (RWGS) conversion under H2 lean conditions - Jagtap, Anuradha Vijay; Bamnia, Mahesh Kumar; Maibam, Ashakiran; Bajpai, Jyotsna Paliwal; Gupta, Sharad; Thomas, Sharon K.; Dabke, Niteen B.; Vinod, C. P. (Chemical Engineering Journal, 2025)
CO2 emissions leading to global warming and environmental and socio-economic issues have propelled the research community to develop technologies capable of capturing and converting CO2 into valuable products. Controlling the selectivity toward platform molecules like CO, methanol, or methane is a fundamental challenge in CO2 hydrogenation. Supported cobalt nanoparticles are known for hydrocarbon production through FischerTropsch (FT) reaction, and Cu-based catalysts are known for reverse water gas shift (RWGS) reaction. Here, we show that d-band centre can be carefully modulated by making bimetallic combinations of Cu and Co for a highly active RWGS catalyst. An oxygen vacancy-rich nanostructured ceria-zirconia (CZ) support with Cu nanoparticles (2 wt%) modified with as low as 0.05 wt% Co shows excellent conversion for CO2 hydrogenation and selectivity for CO below 500 degrees C. The optimized catalyst shows CO2 conversion even under hydrogen lean conditions (H2/ CO2 ratio 0.5:1), with a breakthrough rate of 206023 mmol/gmetal/h for CO at 600 degrees C, having H2 utilization of 80% for the RWGS process.
Keywords: Bimetallic catalyst; Ceria-zirconia; CO 2 hydrogenation; Cobalt catalyst; Copper catalyst; Reverse water gas shift (RWGS); synergistic effect